2010
DOI: 10.1038/ijo.2010.119
|View full text |Cite
|
Sign up to set email alerts
|

Are the feet of obese children fat or flat? Revisiting the debate

Abstract: Objective: There is debate as to the effects of obesity on the developing feet of children. We aimed to determine whether the flatter foot structure characteristic of obese primary school-aged children was due to increased medial midfoot plantar fat pad thickness (fat feet) or due to structural lowering of the longitudinal arch (flat feet). Methods and procedures: Participants were 75 obese children (8.3±1.1 years, 26 boys, BMI 25.2±3.6 kg m À2 ) and 75 age-and sex-matched non-obese children (8.3 ± 0.9 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 17 publications
(23 reference statements)
4
44
0
2
Order By: Relevance
“…Based on the conducted study, they recognised that lower plantar arch height found in the overweight/obese children suggests that the flatter feet characteristic of overweight/obese preschool children may be caused by structural changes in their foot anatomy. Riddiford-Harland et al [18] considered whether the feet in obese children are flat or fat. The authors' findings indicate that obese children had significantly greater medial midfoot fat pad thickness relative to the leaner children during both non-weight bearing and weight bearing.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the conducted study, they recognised that lower plantar arch height found in the overweight/obese children suggests that the flatter feet characteristic of overweight/obese preschool children may be caused by structural changes in their foot anatomy. Riddiford-Harland et al [18] considered whether the feet in obese children are flat or fat. The authors' findings indicate that obese children had significantly greater medial midfoot fat pad thickness relative to the leaner children during both non-weight bearing and weight bearing.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and functional development of the foot are influenced by internal factors (sex, genetics, and age) and external factors (footwear habits, loading, and physical activity (Echaari and Forriol 2003). Because the foot structure of children is not fully developed, the influence of ill-fitting shoes can prevent the normal development of the foot and result in problems and pathologies in both childhood and adulthood (Riddiford Harland et al 2011) Therefore, footwear should be designed to satisfy the foot dimensions of children, according to the characteristics of the population (Jiménez-Ormeño et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gano and Panahal also concluded that obesity reduced the internal length of the arch due to the excessive overload of the weight forces, and thus had a negative effect on the index of the arch of the foot (25). A Harland study on obese children showed that the index of the arch was significantly longer and wider than its normal counterparts [26].…”
Section: Discussionmentioning
confidence: 99%